Dietary Behavior of The Elderly on Era 4.0 - ทองสุก, ทองใหม่ (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The purposes of this research were to: 1) study the dietary behavior of long-living elderly on era 4.0 and 2) the relationship between personal factors such as: gender, age, BMI and dietary behavior. The samples are 29 of long-living elderly on era 4.0 with ages more than 80 years old living in Tambon Thaphilang, Muang district, Suphanburi province. The long-living elderly must be able to questions. The statistics used to analyze data in this research are frequency, percentage, and (Chi-square: χ 2) The data were analyzed using statistical tools. As for their dietary behavior on era 4.0,It was found that most long-living elderly usually have five food groups. eggs, UHT, milk, Paddy, cabbage, watermelon, papaya, and vegetable oils, They purchased these five groups of food for consumption. Boiling was the main method of cooking. They usually stored food in the refrigerator to keep them fresh. The relationship between personal factors and dietary behavior could be classified into 5 areas: types of food, frequency of consumption, sources of food, methods of cooking and methods of food preservation. The finding found that gender, age and BMI were related with food consumption. However, cooking (boiling) was not related with statistically significant level at .05.